NEGASI (An-Nafy) DAN INTROGASI (al-Istifhām) DALAM PENAFSIRAN AL-QUR’AN - Murjani Murjani (CV. Adiba Aisha Amira, 2022)
Istihfam is an attempt made by the questioner to get answers to what he does not know or understand. Istifham is divided into two parts, namely in the form of isim and letters. As for the form of isim, then there are nine kinds, while those in the form of letters are of two kinds. Istifham is essentially an effort to gain understanding by asking things that are not known or understood, but sometimes the nature of the use of Istifham can change if what the questioner wants is known, this adjusts to the context of the existing sentence. The change in nature is as we have explained above.